The Effectiveness of Written Arabic Method Based on Contextual Learning on Arabic Education Student at The Islamic Institute of Jember - Bambang Irawan (Universitas Yudharta Pasuruan, 2020)
Over several years, the researcher noted that the students in the Arabic Education of State Islamic Institute of Jember were bored with teaching and learning writing skills, and the competence of this skill is low. This research aims to: (1) produce a module in Arabic Writing Teaching Based on The Contextual Teaching Learning that called "al-Kitabah al-Muyassarahlil-Mubtadi'in", (2) find out the level of appropriateness of the use of the module to improve students the competence, (3) describe the effect of the module for students motivation. This research used a method named research and development with the Borg and gall's model. The data were collected through observation, interviews, tests, questionnaires, and document studies. The researcher's analysis was done descriptively for qualitative and statistical information for quantitative data. This research resulted in (1) product in a module based on five characteristics: vocabularies writing, illustrated sentences are writing, pattern sentences, expressions writing, Structures, paragraphs writing, and reflection (2) the module is invalid to improve students' writing competence, and (3) the module based on Contextual Teaching Learning can improve student's motivation.